13.8k views
7 votes
Solve for N,

−2p + 6n = 5

User Priojewo
by
5.9k points

1 Answer

6 votes

Answer:


n=(1)/(3)p+(5)/(6)

Explanation:

In this question, you are solving for n.

Solve:

−2p + 6n = 5

We have to get "n" by itself, so add 2p to both sides.

6n = 2p + 5

Since the variable "n" has a number next to it, we have to get rid of that number in order to get our answer.

To do so, we would divide both sides by 6.


n=(2)/(6)p+(5)/(6)

Simplify the equation further.


n=(1)/(3)p+(5)/(6)

User Fraiser
by
5.8k points